(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Depending on the location of Fergana region and climatic conditions, cotton with medium fiber seed is planted in this area. Based on this, more emphasis should be placed on the selection of cotton varieties grown in order to obtain a large yield from the cultivated fields. Also, increasing crop productivity and productivity in the case of using a good selection variety